Individual variation in plasma oxytocin and vasopressin levels in relation to the development of combat-related PTSD in a large military cohort. (November 2017) - Reijnen, Alieke; Geuze, Elbert; Vermetten, Eric
Abstract: In an attempt to decrease the risk of developing mental health problems after military deployment, it is important to find biological markers to identify those at risk. Oxytocin (OT) and arginine vasopressin (AVP) are potential biomarkers for the development of posttraumatic stress disorder (PTSD) because they are involved in the regulation of stress and anxiety. Therefore, the aim was to examine whether plasma OT ( p OT) and AVP ( p AVP) levels before and after deployment are biomarkers for the development of posttraumatic stress symptoms over time in addition to other known risk factors. This study is part of a large prospective cohort study on candidate markers for stress-related mental health symptoms and resiliency after deployment to a combat zone; Prospective Research in Stress-related Military Operations (PRISMO; N = 907). Data was collected prior to deployment and follow-ups were performed at 1 and 6 months, and 1, 2, and 5 years post-deployment. Blood samples were collected in the first three assessments. The levels of p OT and p AVP were not significantly related to the development of PTSD symptoms over time. The results confirm that age, the experience of early life trauma, combat-related stressors and the presence of depressive symptoms are predictive for the development of PTSD symptoms over time. These findings showed that peripherally measured OT and AVP currently do not qualify as useful susceptibility biomarkers for the development of PTSD symptoms over time in military men after combat.